2017
DOI: 10.1080/23766808.2017.1346548
|View full text |Cite
|
Sign up to set email alerts
|

Camera traps provide valuable data to assess the occurrence of the Great Curassow Crax rubra in northeastern Costa Rica

Abstract: The Great Curassow (Crax rubra) is an endangered species in Costa Rica due to habitat loss and hunting pressure. Little is known about the spatial ecology of cracids and there is a need to assess their distribution to establish efficient conservation strategies. In this study, we integrated camera trapping data with occupancy models to examine landscape factors that affect the distribution of the Great Curassow in the San Juan-La Selva Biological Corridor in Northeastern Costa Rica. We established remote camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
2
9
0
4
Order By: Relevance
“…If we dissect our results according to rivers, occupation was greater than 0.50 at about 2.5 km from Colonia Dalmacia (100 inhabitants) and about 10 km from Mojón de Fierro (3000 inhabitants). This may be due to increased hunting pressure, selective logging, and other disturbances that affect availability of resources and structure of forests (Bennett and Robinson 2000, Putz et al 2000, Azevedo-Ramos et al 2006, Pardo et al 2017. Our results agree with a recent review by Benitez-Lopez et al (2017), who analyzed 176 studies conducted in the tropics and found that game bird populations are depleted, on average, within 7 km of populated areas.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…If we dissect our results according to rivers, occupation was greater than 0.50 at about 2.5 km from Colonia Dalmacia (100 inhabitants) and about 10 km from Mojón de Fierro (3000 inhabitants). This may be due to increased hunting pressure, selective logging, and other disturbances that affect availability of resources and structure of forests (Bennett and Robinson 2000, Putz et al 2000, Azevedo-Ramos et al 2006, Pardo et al 2017. Our results agree with a recent review by Benitez-Lopez et al (2017), who analyzed 176 studies conducted in the tropics and found that game bird populations are depleted, on average, within 7 km of populated areas.…”
Section: Discussionsupporting
confidence: 90%
“…Village distance explained much of the occupancy because it was a good proxy for the two main threats that the Bare-faced Curassow faces along the gallery forest of the rivers. In other studies, distance to populated areas has been used as a variable of occupancy, assuming that distance can be an indirect measure of anthropic effects on wild animal populations (Arroyo-Rodríguez et al 2008, Marinho et al 2018, Pardo et al 2017. However, in our work, we were able to measure these effects and confirm the direct relationship between hunting and selective logging with village distance.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The male-biased capture ratio of Great Curassows in our study supports the success of programs to eliminate hunting at Osa Verde. Given their striking bill coloration and easy detection during mating displays, males are more easily detected and killed by hunters (Pardo et al 2017). Consequently, where hunting is present, sex ratios are typically skewed toward females (Martínez-Morales et al 2009, Pardo et al 2017.…”
Section: Discussionmentioning
confidence: 99%